A Compact Frequency and Radiation Reconfigurable Antenna for 5G and Multistandard Sub-6 GHz Wireless Applications. (10th February 2022) - Ullah, Shakir; Elfergani, Issa; Ahmad, Inzamam; Din, Iftikhar Ud; Ullah, Sadiq; Rehman Khan, Wasi Ur; Ahmad, Toufeeq; Habib, Usman; Zebiri, Chemseddine; Rodriguez, Jonathan
Abstract : This paper presents a reconfigurable antenna operating in three modes at different frequency bands with pattern reconfiguration. Frequency and pattern reconfigurability are achieved using four PIN diodes. In particular, two diodes are mounted in the radiating part of the hexagon shape to perform the frequency reconfiguration of the antenna. The other two PIN diodes are connected with the inverted L-shaped and CPW ground by changing the main lobe beam steering to achieve the pattern reconfiguration. An antenna has been designed, fabricated, and numerically and experimentally assessed. The prototype of the antenna is fabricated on a commercially available FR-4 substrate of thickness 1.6 mm (ε r = 4.3). Thus, the proposed antenna supports several 5G sub-6 GHz bands (3.1 GHz, 4.1 GHz, and 3.8 GHz), WiFi (2.45 GHz), as well as (7.8 GHz, 9.5 GHz) X-Band Satellite applications. The obtained results are quite promising. In particular, it is observed that the measured results are in close agreement with the simulation results, and the proposed (compact) antenna prototype can be a prospective candidate for future portable devices, sensor networks, and telecommunication applications.